Influence of Electronic Word of Mouth (WOM) and Brand Image on 'Semangat Coffe' Purchase Intentions - Muhammad Rizky; Puspita Chairun Nisa; Unggul Kustiawan; Ika Baskara (CV. Ulil Albab Corp, 2024)
This study examines the influence of Electronic Word of Mouth (E-WOM) and Brand Image on Purchase Intention in the context of coffee shops in Bekasi, Indonesia. The rising trend of coffee culture among Generation Z has shifted consumer behavior towards frequenting coffee shops over opting for instant coffee. E-WOM has emerged as a key source of information for prospective customers, shaping trust and decision-making through reviews on platforms like Google and social media. Brand Image is another critical factor, shaping consumer perceptions and fostering loyalty through positive brand associations. A quantitative approach with Structural Equation Modeling (SEM) was used to analyze data from a sample of Generation Z consumers. The findings reveal that E-WOM significantly impacts both Brand Image and Purchase Intention, highlighting the role of online reviews in influencing consumers’ decisions to visit coffee shops. Additionally, Brand Image positively affects Purchase Intention, underscoring its importance in driving consumer loyalty and repeat visits. This study extends previous research by focusing on a different cultural and geographical context, contributing to our understanding of how E-WOM and Brand Image shape consumer behavior in the Indonesian coffee shop industry.